Changes in soft tissue profile during the treatment of Class III malocclusion treated with Class III activator (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Objective: This longitudinal retrospective cephalometric study was undertaken in an attempt to evaluate the effect of Class III activator on the soft tissue structures in subjects with skeletal Class III. Methods: The material consisted of cephalometric films of 26 Class III patients (13females and 13 males, with a mean age of 13.58±4.38 years). Each treated patient was matched before treatment with Class III subject for sex and age. Differences at T1 and T2 were examined using paired t-test. Results: After treatment the patients' soft tissue profile improved significantly compare with before treatment. Conclusion: Soft tissue changes were found in patients treated by Class III activator in skeletal Class III patients. Clinical relevance: Class III activator may be an efficient method to improving soft tissue facial profile in Skeletal Class III malocclusion. DOI: http://dx.doi.org/10.3329/bjodfo.v2i2.16160 Ban J Orthod & Dentofac Orthop, April 2012; Vol-2, No.2, 24-29